2018
DOI: 10.1186/s12891-018-2018-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of internet-based decision aids for shoulder arthritis: what are patients reading?

Abstract: BackgroundThe objective of this study was to assess the source, quality, accuracy, and completeness of Internet-based information for shoulder arthritis.MethodsA web search was performed using three common Internet search engines and the top 50 sites from each search were analyzed. Information sources were categorized into academic, commercial, non-profit, and physician sites. Information quality was measured using the Health On the Net (HON) Foundation principles, content accuracy by counting factual errors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…Among the included studies, Google (86%), 5 , 12 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Bing (76%), 5 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 and Yahoo (76%) 5 , 14 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 31 were the most commonly assessed search engines and were used for both website and image searches ( Appendix Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the included studies, Google (86%), 5 , 12 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Bing (76%), 5 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 and Yahoo (76%) 5 , 14 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 31 were the most commonly assessed search engines and were used for both website and image searches ( Appendix Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Somerson et al. 28 specifically considered source accuracy based on website type. They found that commercial websites had the most errors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations